2017
DOI: 10.1002/alr.22045
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the abnormal nasal aerodynamics and trigeminal functions among empty nose syndrome patients

Abstract: This is the first CFD examination of nasal aerodynamics in a large cohort of ENS patients. The results indicated that a combination of loss of neural sensitivity and poorer inferior air-mucosal stimulation may potentially lead to ENS symptomology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
112
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 84 publications
(140 citation statements)
references
References 31 publications
(49 reference statements)
7
112
0
1
Order By: Relevance
“…In fact, a subjectively congested nose may not exclusively have an anatomical origin but might also result from insensitivity of the nasal trigeminal nerve. In this context, it seems possible that the feeling of a decreased patency of the nasal cavity may stem from decreased trigeminal sensitivity [22, 23]. …”
Section: Introductionmentioning
confidence: 99%
“…In fact, a subjectively congested nose may not exclusively have an anatomical origin but might also result from insensitivity of the nasal trigeminal nerve. In this context, it seems possible that the feeling of a decreased patency of the nasal cavity may stem from decreased trigeminal sensitivity [22, 23]. …”
Section: Introductionmentioning
confidence: 99%
“…ENS is commonly associated with inferior turbinate resection (ITR) and rarely associated with middle turbinate resection . CFD airflow investigations after ITR have demonstrated decreased nasal resistance, increased nasal airflow, and decreased SAHF50 . In patients with ENS, CFD simulation showed that small ITs resulted in decreased airflow intensity around the IT.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, patients with empty nose syndrome (ENS) suffer from nasal airway obstruction, chronic nasal crusting, dryness, and fetid odor. This debilitating disease is associated with, and commonly attributed to, previous intranasal surgery performed to correct nasal airway obstruction . Altered aerodynamics causing abnormal conditioning of nasal airflow are thought to contribute largely to the development of ENS .…”
mentioning
confidence: 99%
See 2 more Smart Citations